Strategi Pengembangan Wisata Edukasi di Godong Ijod Depok dengan Experiential Marketing - Mordahai Siburian; Devi Roza K. Kausar; Riza Firmansyah (Journal of Tourism Destination and Attraction, 2017)
Godong Ijo is a visitors’ attraction offering educational tourism programs with quite strong interaction with nature. The programs are designed as a means of learning, hence they are often participated by students. The purpose of this study is to describe the application of experiential marketing in Godong Ijo’s programs from visitors’ perspectives and to develop development strategy for Godong Ijo based on experiential marketing. The method used is qualitative research method using survey, interview and observation as the data collection techniques. Further, data collected were analysed using SWOT analysis. The result of this research reveals that Godong Ijo has tourism potential in terms of attraction, accessibility, amenity, and ancillary. In terms of experiential marketing, most respondents agree that all experiential marketing elements, i.e. think, sense, feel, act, and relate have been delivered to the visitors. Recommendations for development strategy include more extensive promotion, service improvement, product innovation and more product development.